2017
DOI: 10.1002/ijch.201700019
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Transfer Hydrogenation of Ketones Using New Iron(II) (P‐NH‐N‐P′) Catalysts: Changing the Steric and Electronic Properties at Phosphorus P′

Abstract: The asymmetric transfer hydrogenation (ATH) of ketones is an efficient method for producing enantioenriched alcohols which are used as intermediates in a variety of industrial processes. Here we report the synthesis of new iron ATH precatalysts (S,S)-[FeBr(CO)(Ph 2 PCH 2 CH 2 NHCHPhCHPhNC = CHCH 2 PR' 2 )][BPh 4 ] (R' = Et, and orthotolyl (o-Tol)) where one of the phosphine groups is modified with small alkyl and large aryl substituents to probe the effect of this change on the activity and selectivity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Mechanistic investigations and ligand variations with respect to the backbone and phosphorus substituents gave additional insight. [435][436][437] While considerably more active than iron pincer catalysts, the PNNP systems are prone to reduced stereoselectivity due to racemization of the product alcohol. Scheme 34.…”
Section: Asymmetric Hydrogenation Of Ketonesmentioning
confidence: 99%
“…Mechanistic investigations and ligand variations with respect to the backbone and phosphorus substituents gave additional insight. [435][436][437] While considerably more active than iron pincer catalysts, the PNNP systems are prone to reduced stereoselectivity due to racemization of the product alcohol. Scheme 34.…”
Section: Asymmetric Hydrogenation Of Ketonesmentioning
confidence: 99%
“…Later, related catalysts 12 and 13 bearing other phosphine substituents (R 3 = Et, o-Tol) were investigated in these reactions under the same conditions in order to evaluate the role of the steric properties of the phosphine groups on the activity and enantioselectivity. The asymmetric transfer hydrogenation of a range of alkyl aryl and dialkyl ketones was achieved with low to complete conversions (22->99%) and low to high enantioselectivities (12-90% ee), as shown in Scheme 6 [21]. The comparison of the results showed that by increasing the steric bulk at one phosphine (R 3 = Cy or o-Tol instead of Et), the enantioselectivity of the reaction increased.…”
Section: Asymmetric Transfer Hydrogenations Of Ketones and Iminesmentioning
confidence: 98%
“…Such complexes contain an iron(II) center coordinated to a chiral tetradentate P−N−N−P ligand, in which the two nitrogen donors can derive both from imines (complex 8 , Scheme 5A), [26] an imine and an amine (complexes 9 to 11 a – f ) [27] or two amines (complexes 12 a – e , Scheme 5A) [27c] . Complexes 8 – 12 showed noteworthy activity and enantioselectivity in the transfer hydrogenation of ketones: 98% ee , along with a conversion of 71%, was reached in the ATH (asymmetric transfer hydrogenation) of acetophenone to ( R )‐1‐phenylethanol catalyzed by complex 10 (Scheme 5B), and other ketones were reduced with ee s up to 99% [28] …”
Section: Octahedral Complexes In Asymmetric Reduction Reactionsmentioning
confidence: 99%
“…[27c] Complexes 8-12 showed noteworthy activity and enantioselectivity in the transfer hydrogenation of ketones: 98% ee, along with a conversion of 71%, was reached in the ATH (asymmetric transfer hydrogenation) of acetophenone to (R)-1-phenylethanol catalyzed by complex 10 (Scheme 5B), and other ketones were reduced with ees up to 99%. [28] These complexes have been isolated and characterized in the solid state both in the trans (complexes 8-10) and cis-β (complexes 11 a-f and 12 a-e) geometries, the latter with a well-defined helicity. However, the predominant species in solution, which is also the catalytically active one, was the trans-geometry, and thus enantioselectivity can be attributed to the chirality of the PÀ NÀ NÀ P ligands only.…”
Section: Octahedral Complexes In Asymmetric Reduction Reactionsmentioning
confidence: 99%